BergaCare SmartLipids: commercial lipophilic active concentrates for improved performance of dermal products - Olechowski, Florence; Müller, Rainer H.; Pyo, Sung Min (Beilstein Journal of Nanotechnology, 2019)
SmartLipids are the latest generation of dermal lipid nanoparticles with solid particle matrix. Their characteristic properties resulting from the “chaotic” and disordered particle matrix structure are reviewed. These properties are high loading and firm inclusion of active agents, physical stability of the particle matrix lipid modification (primarily α, β′), and related to these three properties the improved chemical stabilization of labile active agents. Exemplarily data for these effects are shown and underlying mechanisms are discussed. Further, general properties of lipid nanoparticles, which are also exhibited by the SmartLipids, are reviewed. These include the restauration of the protective lipid skin barrier (anti-pollution effect), penetration enhancement by occlusion (invisible patch effect) and the option to control the release of active agents for optimized biological effect and reduction of side effects (e.g., skin irritation through sensitizing active agents), which improves the skin tolerability. Regulatory aspects, such as submicron particle status, excipients, and certifications, are also discussed.
Keywords: chemical stabilization of active agents; controlled release; firm inclusion; nanostructured lipid carriers (NLCs); penetration enhancement; skin occlusion; SmartLipids; solid lipid nanoparticles (SLNs)